Noospheric vector of management applied to the system of higher professional education - Yulia A. Mishina; Anna V. Veriga (Открытое образование (Москва), 2017)
The aim of the research is to substantiate the necessity, expediency of the wide use of the noospheric management approaches, and technologies applied to the system of higher professional education in modern conditions. The materials and methods. Information base of the research is formed, based on education laws in Ukraine, Russia and the Donetsk People’s Republic, educational standards of higher professional education, as well as publications of scientists on the subject matter under study. In the given research it was used such methods: textological, analysis, generalization and modeling. The results. In the research, it is comprehensively examined the concept of noosphere, analyzed the modern theories and concepts of its development in relation to the development of society, an integral part of which is the system of education. It is indicated that there is the relationship between the noosphere and management in general, and with modern system of education, in particular. The concept of noospheric education is introduced and studied its impact on holistic  development of personality. The comparative characteristic of the structure and levels of the educational system of Ukraine, the Russian Federation and the Donetsk People’s Republic is performed; the types of educational institutions of the abovementioned states are compared. The structure of educational institution of higher professional education is proposed as a socio-economic system, managed from the perspective of the concept of noospheric education. The factors of competitiveness of educational institution of the higher school from the point of view of noospheric management are considered. Special attention is given to the internal factor of competitiveness of educational institutions, such as the quality of student life, because this position, particularly from the point of view of noospheric management, has a significant influence on the rating among consumers. The interrelation of competences is analyzed – general cultural, first of all, – formed in the process of mastering educational programs, as well as the impact they have on the functions implemented on their basis. The close interrelation is  demonstrated between the models of the functioning of the educational institution of higher professional education with its legislative status. The types of educational institutions of higher school are examined and compared; a special attention is paid to such a type of educational institution as educational-scientific-methodical complex. The purpose and objectives of such complex are systematized. Conclusion. According to the results of the research, it is concluded that the mission of noospheric education lies in the strategic breakthrough into the new quality of thinking technologies, social state, and standards of living. Taking into consideration the noospheric approach to manage the system of higher professional education, its aim is to ensure the training of qualified, competitive personnel, that meet the modern requirements to the quality of specialists with higher education that are capable of independent work on selected  areas of expertise, have high spiritual, cultural and moral qualities, and are able to ensure scientific-technical, economic, social and cultural development of the state. Perspective and social significance of noospheric technologies in education prove the expediency of their widespread introduction into the practice of training of young professionals. The direction of further research indicates the formation, based on the principles of noospheric management, of an innovative strategy for improving the quality of educational services.